Digital Tax Governance in Optimizing Local Own-Source Revenue: Evidence from Kampar Regency, Indonesia - Zamhur, Zamhur; Marantika, Abshor (Dinasti Publisher, 2026)
Fiscal decentralization has become a central policy in many developing countries aimed at improving local government autonomy and enhancing public service delivery. One key indicator of fiscal autonomy is the capacity of local governments to generate Local Own-Source Revenue (Pendapatan Asli Daerah/PAD). However, many local governments in Indonesia still depend heavily on fiscal transfers from the central government. This study examines the role of digital governance in optimizing local tax administration and increasing PAD in Kampar Regency, Riau Province. The research employs a qualitative descriptive approach supported by secondary fiscal data analysis. The findings indicate that digital tax administration contributes to improving transparency, administrative efficiency, and taxpayer compliance. Digital systems allow local governments to monitor tax transactions more effectively while reducing revenue leakage. However, challenges remain in terms of technological infrastructure, human resource capacity, and digital literacy among taxpayers. Strengthening digital governance in local taxation is therefore essential for improving fiscal sustainability and enhancing regional financial independence.